FACE ASSESSMENT LEARNED FROM EXISTING IMAGES IN ORDER TO CLASSIFY THE GENDER OF THE IMAGES BASED ON IMPROVED FACE RECOGNITION (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Face is among the most vital biometric traits. When we study the face, we can gather detailssuch as age and gender, ethnicity, expression, identity, etc. A system for gender classificationuses the faces of people from an image to identify what nature of the gender (male/female)that is the individual. A gender-based approach that is successful can improve theperformance of numerous other applications, including facial recognition and a sophisticatedhuman-computer interface. This paper provides the fundamental processing steps required forgender classification based on face images. In this paper, a variety of techniques employed indifferent stages in gender categorization, i.e., features extraction as well as classification arepresented and contrasted.